2004
DOI: 10.2320/matertrans.45.577
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Eutectic Carbide Content on Erosion Behaviors in Ductile Cast Irons

Abstract: During the casting process of thin-wall parts, due to fast cooling rate or chemical composition of the ductile iron, iron carbide (cementite) may exist in the microstructure that retards the mechanical properties of the iron greatly. In this study we discuss the effects of eutectic carbide contents in relation to the cooling parameters and the erosion behavior of the erosion incident angle on the casting specimens. Different content of eutectic carbide was produced by varying the cooling rate and silicon conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…A matrix with a plastic deformation capability gives an alloy a reasonable wear and impact resistance [14,1617]. Although several carbides give cast iron/steel its excellent wear resistance under dry sliding conditions [15], they can cause a detrimental effect during repeated particle impingements [18]. Stevenson and Hutchings [19] studied the wear of hard-facing white cast irons by solid-particle erosion and concluded that harder particles (SiC and SiO 2 grits) as erodent material caused fracture of primary carbides, resulting in material loss and high wear rates.…”
Section: Introductionmentioning
confidence: 99%
“…A matrix with a plastic deformation capability gives an alloy a reasonable wear and impact resistance [14,1617]. Although several carbides give cast iron/steel its excellent wear resistance under dry sliding conditions [15], they can cause a detrimental effect during repeated particle impingements [18]. Stevenson and Hutchings [19] studied the wear of hard-facing white cast irons by solid-particle erosion and concluded that harder particles (SiC and SiO 2 grits) as erodent material caused fracture of primary carbides, resulting in material loss and high wear rates.…”
Section: Introductionmentioning
confidence: 99%